Mr findings of forgotten surgical ped in surgical area - Peker, Selçuk; Sun, İbrahim; Pamir, M Necmettin (Marmara Medical Journal, 2007)
Foreign body reaction is a specific type of chronic inflamation characterized by granuloma formation. Foreign body granulomas have been reported to cause clinical symptoms anywhere from months to decades after a surgical procedure. Here, we report a case in that a forgotten surgical cotton ped was thought tumoral recurrence and patient undergone craniotomy. In this case report, we emphasized that although it is very rare, granuloma of foreign body reaction can give false image of tumoral recurrence.
Keywords: Foreign body, Meningioma recurrence, Granuloma